»Raziskovanje študentov zdravstvenih ved prispeva k zdravju in razvoju sodobne družbe«: zbornik predavanj: 11. študentska konferenca s področja zdravstvenih ved z mednarodno udeležbo, Maribor, 24. 5. 2019 - Čuček Trifkovič, Klavdija; Mlakar, Ines (2019)
11. Student Conference on Health Sciences with International Participation »Health Sciences Students Research Contributes to Health and Development of Modern Society«, Maribor, 24. 5. 2019. Students contribute to mutual cooperation and strengthening of professional identity for today and for the future. By participating in research, they contribute to the development of knowledge for the health of individuals, families and society. Students’ ability to transfer and apply theoretical knowledge to practice and solve professional problems in a way that is evidence-based and person-centred is fundamental for autonomous professional work at all levels of health care. The Student Conference is an opportunity to promote the development, dissemination and use of knowledge in the field of nursing and health sciences. At 11th Student conference on health sciences with international participation entitled »Health Sciences Students’ Research Contributes to Health and Development of Modern Society«, organized by University of Maribor, Faculty of Health Sciences, students of health sciences from Slovenia and abroad will present papers that were created in the form of project, research, seminar or final work during the course of studies under the mentorship and co-mentorship of higher education teachers.
Keywords: research; education; nursing; health sciences; student conference